Expatriate Family Adjustment: An Overview of Empirical Evidence on Challenges and Resources - Sterle, Mojca Filipič; Fontaine, Johnny R. J.; De Mol, Jan; Verhofstadt, Lesley L. (Frontiers in Psychology, 2018)
The current theoretical paper presents a comprehensive overview of findings from research attempting to understand what happens with expatriates and their families while living abroad. Our paper draws on research on adjustment of individual family members (expatriates, their partners, and children) and families as a whole, across different literatures (e.g., cultural psychology, family psychology, stress literature). The key challenges of expatriation are discussed, as well as family members’ resources. Our findings lead to the following conclusions: First, there is lack of systematic research as studies are either missing a theoretical background or largely neglect the multi-informant approach. A comprehensive theory of expatriate family adjustment integrating multiple theoretical perspectives, including the culture identity formation and the impact of home country and host country culture, is called upon. Second, the majority of studies paid little attention to define the concept of family or failed to take into account the cultural aspect of relocation. Third, there is a call for more longitudinal studies including all family members as adjustment is a process that unfolds over time and therefore cannot be sufficiently explained by cross-sectional studies. Suggestions for future research and practical implications are provided, with a special focus on how families could be assisted during their adjustment process.